2020
DOI: 10.17049/ataunihem.478072
|View full text |Cite
|
Sign up to set email alerts
|

Hemşi̇reli̇k Öğrenci̇leri̇ni̇n Mezuni̇yet Sonrasina Yöneli̇k Mesleki̇ Kaygilari Ve Etki̇leyen Faktörler

Abstract: Bu araştırma hemşirelik öğrencilerinin mesleki kaygılarını ve mesleki kaygıları etkileyen faktörleri belirlemek amacıyla yapıldı. Yöntem: Araştırma Şubat-Nisan 2017 tarihlerinde bir devlet üniversitesi sağlık yüksekokulunda yürütüldü. Veriler hemşirelik bölümünde okuyan 230 öğrenciden toplandı. Veri toplamada öğrencilerin sosyo-demografik özellikleri, mesleği tercih etme ve sürdürme isteği ve mesleki kaygılara yönelik soruları içeren anket formu kullanıldı. Bulgular: Öğrencilerin en fazla kaygılı olduğu ilk üç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
2
5
0
1
Order By: Relevance
“…When the relevant literature is examined, it is seen that the studies on occupational anxiety focus on four groups (policing, teaching, nursing and medical school students). In the studies mentioned above, findings show that task-related occupational anxiety indirectly affects crisis management skills negatively and supports the results of the research (Temel, Çelikkalp, Bilgiç, & Saraçoğlu, 2020;Zedda, & Ieraci, 2015;Uludağ, Taşdöven, & Dönmez, 2014;Cabı and Yalçınalp, 2013;Lee and Graham, 2001). In addition, different crises have their unique requirements.…”
Section: Structural Equation Model Findingssupporting
confidence: 76%
“…When the relevant literature is examined, it is seen that the studies on occupational anxiety focus on four groups (policing, teaching, nursing and medical school students). In the studies mentioned above, findings show that task-related occupational anxiety indirectly affects crisis management skills negatively and supports the results of the research (Temel, Çelikkalp, Bilgiç, & Saraçoğlu, 2020;Zedda, & Ieraci, 2015;Uludağ, Taşdöven, & Dönmez, 2014;Cabı and Yalçınalp, 2013;Lee and Graham, 2001). In addition, different crises have their unique requirements.…”
Section: Structural Equation Model Findingssupporting
confidence: 76%
“…It can be seen that there is no relationship between students' voluntary choice of field of study and their level of anxiety. However, some studies have found that the anxiety levels of students who did not voluntarily choose their major were high (Aktepe Coşar et al, 2023;Temel, Çelikkalp, Bilgiç, & Varol Saraçoğlu, 2020). This may be related to the fact that the student's success, motivation and self-confidence are positively influenced by the student's choice of subject.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly (Aktepe Coşar et the lack of a relationship between income and occupational anxiety in this study may be due to the fact that there are too many middle It can be seen that there is no relationship between students' voluntary choice of eir level of anxiety. However, some studies have found that the anxiety levels of students who did not voluntarily choose their major were high (Aktepe Coşar et al, 2023;Temel, Çelikkalp, Bilgiç, & Varol Saraçoğlu, 2020). This that the student's success, confidence are positively influenced by the student's choice of subject.…”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmada, elde edilen bulgunun nedeni olarak geliri orta düzey olarak düşünülen öğrencilerin büyük çoğunluğu oluşturmaları olduğu Çalışmamızda, okudukları programı üniversite sınav puanı yettiği için seçenlerin mesleki kaygı toplam puan ortalamaları kendi isteğiyle seçenlere göre daha yüksek bulundu. İncelenen bir çalışmada, bizim çalışmamızla paralel dukları bölümü kendi isteği dışındaki faktörlere bağlı olarak seçen öğrencilerde kaygı düzeyinin bölümünü isteyerek seçen öğrencilere göre daha yüksek olduğu tespit edilmiştir (Temel, 2020). Hem bu çalışmada hem de Temel, Çelikkalp, Bilgiç ve Varol'un (2020)…”
Section: Verilerin Değerlendirilmesiunclassified